2022
DOI: 10.3390/nu14204437
|View full text |Cite
|
Sign up to set email alerts
|

Higher Adherence to a Mediterranean Diet Is Associated with Improved Insulin Sensitivity and Selected Markers of Inflammation in Individuals Who Are Overweight and Obese without Diabetes

Abstract: Insulin resistance (IR) and chronic low-grade inflammation are risk factors for chronic diseases including type 2 diabetes (T2D) and cardiovascular disease. This study aimed to investigate two dietary indices: Mediterranean Diet Score (MDS) and Dietary Inflammatory Index (DII®), and their associations with direct measures of glucose metabolism and adiposity, and biochemical measures including lipids, cytokines and adipokines in overweight/obese adults. This cross-sectional study included 65 participants (males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Actually, dietary patterns have a great impact on systemic inflammation; for example, Western dietary patterns characterized by a high caloric content and high fat can lead to significantly elevated systemic inflammation ( 8 ). On the contrary, the Mediterranean diet, a commonly recognized healthy dietary pattern, was found to have anti-inflammation effects ( 9 ). Therefore, it is necessary to establish a comprehensive measurement method to evaluate the dietary inflammatory potential.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, dietary patterns have a great impact on systemic inflammation; for example, Western dietary patterns characterized by a high caloric content and high fat can lead to significantly elevated systemic inflammation ( 8 ). On the contrary, the Mediterranean diet, a commonly recognized healthy dietary pattern, was found to have anti-inflammation effects ( 9 ). Therefore, it is necessary to establish a comprehensive measurement method to evaluate the dietary inflammatory potential.…”
Section: Introductionmentioning
confidence: 99%
“…Koloverou et al ( 24 ) also reported that MD decreased systematic inflammation and increased total antioxidant capacity. Higher MD score was associated with decreased inflammatory markers—lower NF-κB; additionally, the adiponectin level was higher ( 25 ). Additionally, Mitjavila et al ( 26 ) reported that MD protects lipids and DNA from oxidative damages in patients with the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Rey Auditory Verbal Learning Test (RAVLT; 95,138,139). We will administer the RAVLT to assess cognitive bene ts of both interventions, given that both interventions are expected to improve in ammation (140)(141)(142)(143)(144)(145) and that in ammation has been shown to be related to cognitive performance for those with BD (146-148).…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%